Some Recent Developments in Stochastic Volatility Modelling. - Nielsen, O; Nicolato, E; Shephard, N (2002)
This paper reviews and puts in context some of our recent work on stochastic volatility (SV) modelling for financial economics. Here our main focus is on: (i) the relationship between subordination and SV, (ii) OU based volatility models, (iii) exact option pricing, (iv) realized power variation and realized variance, (v) building multivariate models.